Investigating the Relationship between Students' Wellbeing and Reading Achievement: A PISA 2018 Analysis of Indonesian Students' Reading Comprehension - Asirah, Asirah; Saputra, Nizar; Rahman, Fadhlur (PAROLE: Journal of Linguistics and Education, 2023)
Student wellbeing has emerged as one of predictors in improving student learning outcome. Studies have reported that resilience, sense of belonging, and eudaimonia are parts of student wellbeing constructs that contribute to higher student achievement. However, none of the studies tested the relationships between the three variables and student reading achievement. Therefore, this study aims to examine student wellbeing constructs of resilience, sense of belonging, eudaimonia, and the effects on these variables on students’ reading achievement. This study also attempts to provide structural model depicting the interrelationships between students’ wellbeing and student reading achievement. PISA 2018 Indonesia data were used in this study with the total sample of (n = 12,098) 15-year-old students in Indonesia. The data were analyzed by employing structural equation modeling (SEM) technique using IBM SPSS AMOS 26. The findings of this study revealed that resilience, sense of belonging, and eudaimonia significantly and directly influenced student reading achievement, and only eudaimonia had a significant negative impact on reading achievement. The study also indicated that sense of belonging is the best predictor of higher student reading performance